Feasibility and challenges of submerged culture of steelhead trout Oncorhynchus mykiss for open ocean aquaculture in the United States - Chambers, Michael; Coogan, Michael; Doherty, Michael; Rillahan, Chris; Lader, Pal; Howell, Willaim H. (Frontiers in Aquaculture, 2025)
To meet growing seafood demands, the US aquaculture industry will need to consider farming the open ocean in a responsible manner. However, offshore environments can be energetic (seas > 8 m) making it difficult to maintain surface cage systems. To minimize potential storm damage, submerged culture technologies can be employed to safeguard the infrastructure and product. Steelhead trout (Oncorhynchus mykiss) have potential as an offshore species, though they have open air bladders (physostomous), and need access to air to inflate their swim bladders. To address this concern, three experiments were developed to explore the ability of O. mykiss to cope with extended periods of submergence. The studies used small ( 300 g) and large ( 1000 g) trout, in cages that ranged from 3.7 to 68 m3, that were submerged for periods of one to four weeks. Data storage tags (DST), sonar and video were used to quantify their ability to manage with submergence. Results indicated differences in growth, condition, and mortality among the treatments. The study suggests O. mykiss can be submerged for days to weeks with no negative effects, but that submergence times >3 weeks can be detrimental. It is therefore recommended that when culturing O. mykiss in areas exposed to severe storms or hazardous environmental conditions (e.g. harmful algal blooms or icing), submersible cages should be utilized to avoid these events up to 3 weeks.